Ovários anômalos em Passalus convexus Dalman, 1817 (Coleoptera: Passalidae) - Fonseca, Claudio Ruy Vasconcelos da (Acta Amazonica, 1981)
The ovariole number seems to be an important factor in the understanding of evolutionary and behavioral problems. In Passalidae, 2-2 ovarioles appear to be invariable for whole family. Anomalies were rarely found, but included two specimens of Passalus convexus Dalman, which had 2-3 and 2-4 ovarioles respectively.